FRI0298 Treatment Patterns among Adult Systemic Sclerosis Patients in A US Healthcare Claims Population. (15th July 2016) - Gale, S.; Mathew, N.; Lin, C.J.; Jahreis, A.; Sarsour, K.
Abstract : Background: In the United States, systemic sclerosis (SSc) develops in adults at an annual estimated incidence rate of 20 cases per million, and the estimated prevalence is 240 cases per million. 1 Published research on the epidemiology of SSc and common treatments for US SSc patient cohorts is limited. In general, SSc patients are treated based on their specific organ involvement; patients with diffuse skin involvement or severe organ involvement, or both, are treated with systemic immunosuppressive therapy. Objectives: To understand the treatment patterns for and the real-world use of immunosuppressive drugs in adults with SSc using data from a large US healthcare claims database. Methods: The analysis is a retrospective cohort study of patients with SSc diagnosed from 2006 to 2012 using data from Truven Health MarketScan® Research Databases, a medical insurance claims database of insured active employees and their dependents, early retirees, Medicare-eligible retirees, and Medicaid recipients. An SSc diagnosis was determined by ≥1 inpatient claim for an SSc diagnosis ( ICD-9 710.1) or ≥2 outpatient claims for an SSc diagnosis. During the study time period, patients were allowed enrollment gaps of ≤30 days but had to have enrollment data 6 months before and 12 months after the SSc diagnosis. Results: The prevalence of SSc in the MarketScan database from 2006 to 2013 ranged from 204 to 247 cases per million adults who were actively enrolled in health insurance plans. There were 6872 patients ≥18 years of age diagnosed with and treated for SSc during the study time period. Eighty-six percent of the treated SSc population were female, and the average age of the cohort was 54 years. The most common medication claims among patients in the first year after an SSc diagnosis were for antibiotics (54%), opioids (44%), corticosteroids (40%), and proton pump inhibitors (PPIs) (31%). Approximately 30% of SSc patients initiated ≥1 of the following disease-modifying antirheumatic drugs (DMARDs), alone or in combination, in the first year after the SSc index, with a median time to initiation of 70 days: methotrexate (21%), mycophenolate mofetil (17%), biologics (3%), cyclophosphamide (2%), or other DMARDs (62% of which included azathioprine, chloroquine, cyclosporine, hydroxychloroquine, penicillamine, quinacrine, and sulfasalazine). Among patients who filled a DMARD prescription in the first year, 15% switched to a second type of DMARD. Of the 70% of patients who did not fill a prescription for DMARD in the first year after the SSc index, 63% filled prescriptions for antibiotics, 56% opioids, 33% corticosteroids, 26% PPIs, 20% NSAIDs, 10% ACE inhibitors, 10% calcium antagonists, 5% prokinetics, 1% ERA, and <1% prostacyclin. Conclusions: These data show that the prevalence of SSc among adults in a US healthcare claims population is consistent with the estimated US prevalence. Most SSc patients do not initiate DMARD treatment in the first year after diagnosis, and most SSc patients have received antibiotics, opioids, and systemic corticosteroids. References: Mayes MD et al. Prevalence, incidence, survival, and disease characteristics of systemic sclerosis in a large US population. Arthritis Rheum. 2003;48:2246–2255. Disclosure of Interest: S. Gale Shareholder of: Roche, Employee of: Roche, N. Mathew: None declared, C. Lin: None declared, A. Jahreis: None declared, K. Sarsour Shareholder of: Roche, Employee of: Roche